Using conjoint analysis to estimate farmer's preferences for cattle traits in West Africa - Tano, K.; Faminow, M.; Kamuanga, M.; Swallow, B.M. (Elsevier, 2003)
This paper estimates the preferences of farmers for cattle traits in southern Burkina Faso using conjoint analysis, a survey-based system for measuring preferences for multiple-attribute goods. Here the technique is used in the context of a West African country where literacy is low, where cattle perform multiple functions, where low-input management is the norm, and where cattle are exposed to a number of tropical diseases and other environmental stresses. The results reflect the production practices of the region, suggesting that important traits in developing breed improvement programs should include disease resistance, fitness for traction and reproductive performance. Beef and milk production are less important traits. The study shows the potential usefulness of conjoint analysis for quantifying preferences in less developed countries for livestock and for the wide variety of other multiple-attribute goods. One implication is that conjoint analysis provides a quantitative methodology that helps make diverse livelihood strategies more operational. Distinguishing differences in preferences between groups of respondents in connection with specific agro-ecological zones and production systems can be used to promote conservation-through-use of breeds at risk of extinction.